2016
DOI: 10.1039/c6ja00220j
|View full text |Cite
|
Sign up to set email alerts
|

Combined 1D, 2D and 3D micro-XRF techniques for the analysis of illuminated manuscripts

Abstract: The combination of several micro-XRF analysis modes is presented for the investigation of an illuminated parchment manuscript. With a commercial instrument, conventional micro-XRF spot analysis (0D) and mapping (2D) are performed, yielding detailed lateral elemental information. Depth resolution becomes accessible by mounting an additional polycapillary lens in front of an SDD detector. Quantitative confocal depth profiles (1D) are presented as well as the full separation of the front and the backside decorati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 15 publications
(22 reference statements)
1
18
0
1
Order By: Relevance
“…38 The illuminated manuscript has previously been analyzed with a portable Raman-X-ray instrument (PRAXIS) using combined µRaman spectroscopy, µ-XRF and synchrotron µ-XRD, 24 as well as with 3D confocal XRF. 39 Throughout all these studies no visual change to the manuscript folio was noticeable.…”
Section: Illuminated Manuscriptmentioning
confidence: 87%
“…38 The illuminated manuscript has previously been analyzed with a portable Raman-X-ray instrument (PRAXIS) using combined µRaman spectroscopy, µ-XRF and synchrotron µ-XRD, 24 as well as with 3D confocal XRF. 39 Throughout all these studies no visual change to the manuscript folio was noticeable.…”
Section: Illuminated Manuscriptmentioning
confidence: 87%
“…The commercial MXRF spectrometer (Bruker M4 tornado) was equipped with a Rh microfocus X‐ray tube, a polycapillary lens to focus the radiation and a SDD detector (Lachmann et al ). In front of a second SDD a second polycapillary lens was mounted perpendicular to the first, thus creating a confocal MXRF setup which enabled three‐dimensional‐resolved measurements with a resolution of 30 µm at Fe Kα (Mantouvalou et al ).…”
Section: Methodsmentioning
confidence: 99%
“…The false color images, with red indicating pigments on the recto side of the manuscript (further from the detector) and green on the verso side, show the artistic interplay of the two pigments: areas of the scrollwork that have been painted with azurite on the front side are gilded on the back side and vice versa (Figure 6A and B). Confocal XRF analyses previously conducted on the illuminated parchment have shown that the gold layer is very thin (< 1 µm) 32 so that the average thickness of the parchment can be estimated from the gold histograms and is about 120 µm. Indeed, only the parchment separates the gilding on the recto and verso sides.…”
Section: Depth-selective Informationmentioning
confidence: 99%